THE SYSTEM MODEL OF THE PROFESSIONAL SUCCESS FACTORS OF THE ATHLETES IN HIGH PERFORMANCE SPORT - Sukhareva, D.S.; Oboznov , А.А. (Modern Psychology, 2020)
In this article, the authors present a theoretical substantiation of the system model of the professional success factors of the athletes in high performance sport, as well as  its empirical confirmation. The model is a system of factors of professional success of athletes, reflecting in its essence not only a compressed model of professionalization, but also a compressed model of life in general. The development of an athlete in high performance sport, is seen in the determination of past, present and future; where the past is in the form of conditions, causality (motives for choosing a sports career), the present is characterized by functional dependence (connection of life-sense orientations and individual-typological features, sports injury and the influence of these factors on professional success), the future is in the form of goals, the beginnings of the future (planned duration of competitive activity, professional and life plans).
Keywords: professional success, high performance sport, life meaningful orientations, individual and typological features, factors.